Awareness and Practice Regarding Weaning Among Mothers of Under two Years Children at Tertiary level Hospital - Mulepati, Sumitra; Lama, Sumana; Bhandari , Sushila (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Weaning describes how a baby moves or shifts from having breast milk to consuming semi-solid or solid foods with a gradual reduction in breast milk and baby formula intake. The study aims to assess the level of awareness, practice, and association between awareness and practice regarding weaning among mothers of under two years of children. Methods: This descriptive cross-sectional study was conducted in Shree Birendra Hospital, Chhauni, Kathmandu. Mothers having under two years children visiting the Paediatric OPD of Shree Birendra Hospital, Chhauni, were included. Descriptive analysis of data was performed. Results: The total number of samples was 96, and the response rate was 100%. Majority (55.2%) of the respondents were between 26 to 30 years of age, and two third (66.7%) had two children. The majority (65.6%) of the respondents have an average level of awareness regarding weaning. Most (55.2%) of respondents had good practice on weaning. However, there was a nonsignificant association between awareness and practice regarding weaning among mothers under two years of children with selected demographic variables. Conclusions: The mothers of under two years child had an average level of awareness and practice regarding weaning, with a notable association between their awareness levels and actual weaning practices.